Synthesis of High-Purity Silica Nanoparticles by Sol-Gel Method - S. V. Lazareva; N. V. Shikina; L. E. Tatarova; Z. R. Ismagilov (Eurasian Chemico-Technological Journal, 2017)
Colloidal silica (silica sol) nanoparticles were synthesized by ammonia- and hydrochloric acid-catalyzed hydrolysis of tetraethoxysilane with subsequent condensation and polymerization. Silica particles with the size of 12‒160 nm were obtained at different temperatures and ratios of the initial reactants and studied by means of TEM, AFM, IR spectroscopy and zeta-potential measurements. The reaction conditions providing the minimum particle size in the final product of the most complete hydrolysis were determined. At pH above 8.5, an increase in the SiO2 content of the sol to 23 wt.% did not change the particle size. At a low (~ 1.8 wt.%) SiO2 content of the sol, a wide variation in pH also did not exert a significant effect on the particle size. Stability of the silica sols synthesized in an alkaline medium was enhanced by the replacement of alcohol with water during evaporation at pH 8.5‒9.5. The possibility to produce silica sols with the required characteristics (particle size, pH, stability, purity, and SiO2 content in an aqueous or alcohol medium) makes them applicable in various industries.